Humoral response to SARS-CoV-2 vaccines among healthcare workers in a tertiary hospital in Malaysia - Mohd Amin, Amrina; Mukhtar, Shahidah; Razak, Sofiah Hanis; Che Mamat, Mirlia Suzila; Ramasamy, Thilakaveni; Cheah, Yoke Kqueen; Mahmud, Aidalina; Mohd Taib, Niazlin; Amin Nordin, Syafinaz; Abdullah, Maha; Mohd Isa, Muhammad (Malaysian Medical Association, 2022)
Introduction: Healthcare workers (HCWs) were among the first to be fully vaccinated against SARS-CoV-2. However, the antibody responses to the vaccines and potential decline among Malaysian HCW are still unclear. The objective of this study is to follow-up anti-S antibody levels among HCW vaccinated with mRNA vaccine (BTN162b2) and inactivated vaccine (CoronaVac). Materials and Methods: Plasma samples were collected prevaccination, 2 weeks and 6 months post-vaccination and tested for total immunoglobulin levels using ELISA method. Results: A small percentage of HCW (2.2%, 15/677) had elevated anti-S antibody levels in their pre-vaccination plasma samples (median 20.4, IQR 5.8), indicating that they were exposed to SARS-CoV-2 infection prior to vaccination. The mRNA vaccine significantly increased anti-S levels of both previously infected and uninfected individuals to saturation levels (median 21.88, IQR.0.88) at 2 weeks postsecond dose of the vaccine. At 6 months post-vaccination, the antibody levels appeared to be maintained among the recipients of the mRNA vaccine. However, at this time point, anti-S antibody levels were lower in individuals given inactivated vaccine (median 20.39, IQR 7.31, n=28), and interestingly, their antibody levels were similar to anti-S levels in pre-vaccination exposed individuals. Antibody levels were not different between the sexes. Conclusion: Anti-S levels differ in individuals given the different vaccines. While further study is required to determine the threshold level for protection against SARSCoV-2, individuals with low antibody levels may be considered for boosters.